2019
DOI: 10.1039/c8cy01877d
|View full text |Cite
|
Sign up to set email alerts
|

The role of nanosized zeolite Y in the H2-free catalytic deoxygenation of triolein

Abstract: The reduction in zeolite Y crystal size has improved the triolein conversion, yield of deoxygenated product and diesel range hydrocarbon selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…XRD patterns of MZMs (as shown in Figure 2A ) show that the MZMs are largely amorphous with the typical broad signal corresponding to silica at around 25° 2θ. However, the crystalline phase of the parent Y is still preserved to a very small extent, as evidenced by the remaining Y zeolite (111) (2θ = 6.2°), (331) (2θ = 15.6°), and (533) (2θ = 23.8°) planes in MZMs (Aghakhani et al, 2014 ; Choo et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…XRD patterns of MZMs (as shown in Figure 2A ) show that the MZMs are largely amorphous with the typical broad signal corresponding to silica at around 25° 2θ. However, the crystalline phase of the parent Y is still preserved to a very small extent, as evidenced by the remaining Y zeolite (111) (2θ = 6.2°), (331) (2θ = 15.6°), and (533) (2θ = 23.8°) planes in MZMs (Aghakhani et al, 2014 ; Choo et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The parent Y65 was synthesized according to our previous work [ 39 ]. Briefly, solution A was prepared by dissolving NaOH (1.500 g, 99%, Merck, Darmstadt, Germany) and sodium aluminate (2.693 g, 53.0% Al 2 O 3 , 42.5% Na 2 O, Sigma-Aldrich, Malaysia) in distilled water (13.000 g).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we reported that the nanosized zeolite NaY could improve the deoxygenation performance of triolein in the absence of a hydrogen source [ 39 ]. In this study, we extend the utilization of nanosized zeolite NaY by loading with NiO nanoparticles prepared using different synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this is not surprising because most of the accessible basic sites, namely [Si-O-Al] − K + , are located at the external surfaces of the zeolite particles. As a result, K-MER zeolite with smaller crystallite size exhibited a larger number of basic sites [38]. In addition, the low Si/Al ratio of the zeolite framework also contributed to the basicity of K-MER zeolite because when the Si/Al ratio is low, more K + cations are needed by the zeolite for surface charge counter-balance, which leads to the enhancement of zeolite basicity.…”
Section: Morphological Effects On the Catalytic Behavior Of K-mer Zeomentioning
confidence: 99%